Penerapan Alat Cuci Tangan Guna Pencegahan Penyebaran Virus COVID-19 di Desa Lagaruda - Muhammad Yahya; Fathahillah Fathahillah; Rissa Megavitry (Universitas Negeri Makassar, 2020)
Partners of the Community Partnership Program (PKM) are people in Laguruda Village where the community in reality does not fully understand and know the procedures for preventing the spread of COVID-19 infection according to WHO standards. The problems are: (1) lack of knowledge on how to prevent the spread of COVID-19 according to WHO recommendations, (2) lack of knowledge on how to wash hands as recommended by WHO, (3) lack of hand washing facilities used to prevent the spread of COVID-19, and (4) not yet available practical hand washing tools to prevent the spread of COVID-19 . The external targets are (1) the people of Laguruda village understand how to wash hands properly according to WHO standards and (2) be able to reproduce practical hand washing tools that can be placed anywhere as an effort to prevent the spread of COVID-19.. The methods used are: lectures, demonstrations, discussions, questions and answers, and companion partners. The results achieved are (1) partners have knowledge of how to prevent the spread of COVID-19, (2) partners have adequate hand washing facilities to prevent the spread of COVID-19, and (3) partners have practical hand washing facilities to prevent the spread of COVID-19.